STRATEGI PENGUATAN KOMPETENSI SUMBER DAYA MANUSIA UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA (STUDI KASUS: DESA IGAL KECAMATAN MANDAH) - Mhd Alhapiz; Muchlis; Raju Maulana (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2026)
This study aims to analyze the strategy for strengthening human resource competencies in improving the welfare of the community in Igal Village, Mandah District. This research uses a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation involving 44 informants selected using simple random sampling. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña. The results show that the quality of human resources in Igal Village is still relatively low, as indicated by the dominance of basic education levels, limited and traditional work skills, and low technical knowledge and innovation capacity. These conditions have an impact on community welfare, which is not yet optimal, as reflected in unstable income, limited employment opportunities, and moderate quality of life. Although the village government has implemented several empowerment programs, their effectiveness remains limited due to low community participation. Therefore, more targeted and sustainable strategies for strengthening human resource competencies are needed to improve community welfare.